Effect of argon plasma on repair bond strength using nanofilled and microhybrid composites. Issue 5 (21st April 2021) - Negreiros, William Matthew; Ayres, Ana Paula Almeida; Willers, Amanda Endres; Hirata, Ronaldo; Giannini, Marcelo
Abstract: Objectives: To evaluate the effect of atmospheric pressure plasma (PLA), sandblasting (SAN), silanization (SIL) and hydrophobic bonding resin (HBR) on the micro‐shear bond strength (MSBS) of fresh nanofilled (NF) or microhybrid (MH) composites to water‐aged nanofilled composite. Materials and methods: NF plates were fabricated and stored in distilled water for 4 months. The aged plates were assigned to the groups ( n  = 6): 1‐ untreated; 2‐ SAN + SIL + HBR; 3‐ HBR; 4‐ PLA + HBR; 5‐ SAN + HBR; 6‐ SAN + PLA + HBR; and 7‐ PLA. Two fresh composite cylinders were constructed on each plate with NF or MH composites and tested after 24 h or 1 year of water‐storage, using the MSBS testing. Data were analyzed by three‐way ANOVA and Tukey test (α = 0.05). Results: NF yielded better outcomes than MH at 24 h, which was not observed at 1 year. HBR showed the highest MSBS results, while untreated and PLA groups yielded the lowest one. MSBS reduced for all groups after 1 year. Conclusions: Only HBR can obtain good MSBS results, while PLA alone was not beneficial. After 1 year, a reduction in repair MSBS was observed and the type of composite did not influence the results. Clinical relevance: The repair technique can be simplified with the use of only an adhesive and macromechanical retentions in the old composite, regardless the type of fresh composite.